2018
DOI: 10.1016/j.neuro.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Brain derived neurotrophic factor (BDNF), its tyrosine kinase receptor B (TrkB) and nicotine

Abstract: Nicotine is the major neurotoxicant in cigarettes that affects many transmitter systems within the brain as well as other factors, including the growth factors. Brain derived neurotrophic factor (BDNF), is the most abundant growth factor in the brain and plays a critical role in early new neuron differentiation, development and synapsis growth, and the survival of fully developed neurons and synaptic activity. Over the past 3 decades, data has emerged on the effects of nicotine and cigarette smoke exposure on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 157 publications
(147 reference statements)
1
32
0
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) is the most widely distributed neurotrophin in the CNS and is important for cellular growth, development, survival and synaptic activity [ 107 , 108 ]. All these actions are mediated by the selective binding of BDNF to the tyrosine kinase receptor B (TrkB) [ 108 ]. A reduced BDNF signaling through TrkB leads to spatial memory deficits [ 107 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is the most widely distributed neurotrophin in the CNS and is important for cellular growth, development, survival and synaptic activity [ 107 , 108 ]. All these actions are mediated by the selective binding of BDNF to the tyrosine kinase receptor B (TrkB) [ 108 ]. A reduced BDNF signaling through TrkB leads to spatial memory deficits [ 107 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…BDNF is part of the neurotrophin family and via binding with tropomyosin receptor kinase B (TrkB) promotes neuronal development, modulates synaptic function, and regulates synaptic plasticity (Park and Poo ; Nakahata and Yasuda ). A number of studies have examined BDNF in response to acute exposure, seeking, dependence, and relapse to EtOH or NIC (Logrip et al ; Machaalani and Chen ). However, preclinical research has demonstrated a relationship between BDNF expression and drug‐related changes in the brain that is dependent upon a variety of factors including duration of exposure, drug dose, and ROI (Lu et al ; Logrip et al ; Vargas‐Perez et al ; Bobadilla et al ; Haun et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the neuronal growth factors affected by nicotine is BDNF, which plays a principal role in the expression and support of synaptic plasticity including LTP (Figurov et al, 1996;Ying et al, 2002). BDNF is the most abundant neuronal growth factor in the brain (Webster et al, 2002;reviewed in Cunha et al, 2010;Machaalani and Chen, 2018). BDNF produces its positive effects on neuronal development, growth and synaptic plasticity through activation of tyrosine kinase receptor B (Fayard et al, 2005), which eventually leads to involvement of cAMP-response-element-binding protein (CREB) to regulate genes expression involved in the expression and support of LTP (Ernfors and Bramham, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have provided strong evidence showing that exposure to nicotine leads to increased brain BDNF levels (Zhang et al, 2010;Suriyaprom et al, 2013;Jamal et al, 2015;Neves et al, 2017; for review, see Machaalani and Chen, 2018). The expression of BDNF and its tyrosine kinase receptor B receptor are linked to a7nAChRs where evidence shows BDNF and nAChRs mutually influencing each other (Freedman et al, 1993;.…”
Section: Discussionmentioning
confidence: 99%